HEORETICAL AND METHODOLOGICAL APPROACHES TO ASSESSING NATURAL AND GEOGRAPHICAL FACTORS IN TOURISM DEVELOPMENT - Odiljon Tobirov; Xidoyatkhon Abdinazarova; Azamjon Jobborov (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article examines theoretical and methodological approaches to assessing natural and geographical factors influencing tourism development. Based on a synthesis of contemporary scientific literature, the study analyzes key theoretical frameworks that explain the role of natural conditions, geographical location, and environmental resources in shaping tourism attractiveness and sustainability. Special attention is given to modern methodological tools, including Geographic Information Systems (GIS), multi-criteria decision analysis, and integrated qualitative–quantitative approaches used to evaluate tourism potential. The findings highlight that effective tourism development requires a holistic assessment framework that combines ecological, socio-economic, and spatial factors. The study emphasizes that adapting assessment methodologies to regional characteristics enhances strategic planning, supports sustainable tourism practices, and improves policy decision-making. The article contributes to tourism geography by systematizing existing approaches and outlining methodological directions for future research aimed at resilient and environmentally responsible tourism development.